A novel bifunctional GH51 exo-α-l-arabinofuranosidase/endo-xylanase from Alicyclobacillus sp. A4 with significant biomass-degrading capacity. Issue 1 (December 2015) - Yang, Wenxia; Bai, Yingguo; Yang, Peilong; Luo, Huiying; Huang, Huoqing; Meng, Kun; Shi, Pengjun; Wang, Yaru; Yao, Bin
Abstract Background Improving the hydrolytic performance of xylanolytic enzymes on arabinoxylan is of importance in the ethanol fermentation industry. Supplementation of debranching (arabinofuranosidase) and depolymerizing (xylanase) enzymes is a way to address the problem. In the present study, we identified a bifunctional α-l -arabinofuranosidase/endo-xylanase (Ac-Abf51A) of glycoside hydrolase family 51 inAlicyclobacillus sp. strain A4. Its biochemical stability and great hydrolysis efficiency against complex biomass make it a potential candidate for the production of biofuels. Results The gene encoding Ac-Abf51A was cloned. The comparison of its sequence with reference proteins having resolved 3D-structures revealed nine key residues involved in catalysis and substrate-binding interaction. Recombinant Ac-Abf51A produced inEscherichia coli showed optimal activity at pH 6.0 and 60 °C with 4-nitrophenyl-α-l -arabinofuranoside as the substrate. The enzyme exhibited an exo-type mode of action on polyarabinosides by catalyzing the cleavage of α-1, 2- and α-1, 3-linked arabinofuranose side chains in sugar beet arabinan and water-soluble wheat arabinoxylan and α-1, 5-linked arabinofuranosidic bonds in debranched sugar beet arabinan. Surprisingly, it had capacity to release xylobiose and xylotriose from wheat arabinoxylan and was active on xylooligosaccharides (xylohexaose 1.2/mM/min, xylopentaose 6.9/mM/min, and xylotetraose 19.7/mM/min), however a lower level of activity. Moreover, Ac-Abf51A showed greater synergistic effect in combination with xylanase (2.92-fold) on wheat arabinoxylan degradation than other reported enzymes, for the amounts of arabinose, xylose, and xylobiose were all increased in comparison to that by the enzymes acting individually. Conclusions This study for the first time reports a GH51 enzyme with both exo-α-l -arabinofuranosidase and endo-xylanase activities. It was stable over a broad pH range and at high temperature, and showed greater synergistic effect with xylanase on the degradation of wheat arabinoxylan than other counterparts. The distinguished synergy might be ascribed to its bifunctional α-l -arabinofuranosidase/xylanase activity, which may represent a possible way to degrade biomass at lower enzyme loadings.